Severe skin inflammation leads to salivary gland atrophy and dysfunction. Issue 6 (7th March 2022) - Matsushima, Yoshiaki; Mizutani, Kento; Iida, Shohei; Ichishi, Masako; Nakanishi, Takehisa; Okada, Karin; Umaoka, Ai; Kondo, Makoto; Habe, Koji; Watanabe, Masatoshi; Yamanaka, Keiichi
Abstract: Psoriasis and atopic dermatitis are inflammatory skin diseases, and these patients have an increased risk of cardiovascular events and other medical complications. It has been clarified that skin inflammation affects internal organs. Additionally, dental caries tends to occur more frequently in patients with psoriasis and atopic dermatitis. In this study, we aim to investigate the effects of dermatitis on the salivary glands using an inflammation model mouse. Salivary secretion stimulated with pilocarpine was reduced in dermatitis mice. Histologically, dermatitis mice showed amyloid deposition, glandular atrophy, and fibrosis in the salivary glands. Expression of inflammatory cytokines in the salivary glands was higher in dermatitis mice; however, secretion of cytokines in saliva was not significantly different. Dermatitis mice showed decreased salivary secretion and histological changes, which may cause periodontal disease. Therefore, appropriate control of skin inflammation is essential.